The use of audio-visual aids to reduce delirium after cardiac surgery in intensive care units (DaCSi-ICU): A feasibility study protocol - Maria Joao De Azinheira Reguenga; Smaragda Lampridou; Natalie Pattison; Stephen James Brett; Sanooj Soni (PLoS ONE, 2025)
Introduction Delirium can affect over 50% of patients following cardiac surgery in intensive care units (ICU), leading to an increased risk of long-term cognitive impairment, prolonged hospital stays and increased costs. Nurse-led auditory-visual stimulation to help prevent and manage ICU delirium is a novel, unexplored strategy in postoperative cardiac surgical patients but proven to be effective in other long-term conditions. The Delirium after Cardiac Surgery in the Intensive Care Unit (DaCSi-ICU) study aims to assess the feasibility and acceptability of implementing an innovative, family-focused auditory-visual intervention to reduce delirium in ICU patients following major cardiac surgery. Methods and analysis This is a pilot, mixed-methods, non-randomised feasibility study to be delivered in a university hospital cardiac ICU. The primary outcome is to explore the feasibility and acceptability of an innovative family-focused intervention to reduce ICU delirium rates in patients following cardiac surgery. Secondary outcomes are to: explore short-term post-surgical outcomes up to three months of hospital discharge; and investigate participants’ perspectives of taking part in the study. A total of 12 patients, alongside 12 family members or significant others and 6 ICU nurses will be recruited. Demographic data will be reported descriptively, and clinical data will be managed statistically through SPSS. Data collected from interviews will be transcribed full verbatim and analysed on NVIVO using framework analysis. This study has received Health Research Authority (HRA) approval (24/YH/0011). Imperial College Healthcare NHS Trust is the sponsor for research governance purposes. This trial is registered at ClinicalTrials.gov (NCT06355570). Findings will be disseminated through peer-reviewed open-access journals and presented in national and international scientific meetings. Findings will also be shared with patients and the clinical team. Study results will determine the feasibility and acceptability of the intervention, facilitating the progression to a future controlled effectiveness trial.